2023
DOI: 10.21037/tau-23-65
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel 5 cuproptosis-related long noncoding RNA signature to predict diagnosis, prognosis, and drug therapy in clear cell renal cell carcinoma

Abstract: Background: Cuproptosis has been reported as a new form of cell death. However, its potential mechanism of action in clear cell renal cell carcinoma (ccRCC) remains unclear. Therefore, we systematically clarified the role of cuproptosis in ccRCC and aimed to develop a novel signature of cuproptosis-related long noncoding RNAs (lncRNA) (CRLs) to assess the clinical characteristics of ccRCC patients.Methods: Gene expression, copy number variation, gene mutation, and clinical data for ccRCC were obtained from The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Research has shown that SNHG17 is intimately connected to the growth, invasion, migration, resistance to chemicals, and apoptosis of tumor cells, and head and neck squamous cell carcinoma patients whose SNHG17 expression was high had a significantly unfavorable prognosis [17]. Studies showed that lncRNA AC103706.1 is associated with fat metabolism, copper apoptosis, and prognosis in ccRCC [51,52]. However, the relationship between six SRlncRNAs and CSCs has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that SNHG17 is intimately connected to the growth, invasion, migration, resistance to chemicals, and apoptosis of tumor cells, and head and neck squamous cell carcinoma patients whose SNHG17 expression was high had a significantly unfavorable prognosis [17]. Studies showed that lncRNA AC103706.1 is associated with fat metabolism, copper apoptosis, and prognosis in ccRCC [51,52]. However, the relationship between six SRlncRNAs and CSCs has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of renal clear cell carcinoma (RCCC) is intricately linked to the immune system, with a particular emphasis on the distribution and function of T cells within the tumour microenvironment, exerting a direct influence on RCCC's growth and dissemination. 9 , 10 , 11 However, the heterogeneity within these T‐cell populations remains a subject warranting more comprehensive exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Precision medicine, when applied to renal clear cell carcinoma, signifies a tailored and efficacious treatment paradigm, with the potential to enhance both patient survival and quality of life. The progression of renal clear cell carcinoma (RCCC) is intricately linked to the immune system, with a particular emphasis on the distribution and function of T cells within the tumour microenvironment, exerting a direct influence on RCCC's growth and dissemination 9–11 . However, the heterogeneity within these T‐cell populations remains a subject warranting more comprehensive exploration.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been implicated in facilitating the evasion of immune surveillance by tumor cells through multiple mechanisms, including the promotion of an immunosuppressive microenvironment 26 28 . Multiple studies used comprehensive analysis to determine the functions of various lncRNAs in tumor immune microenvironment (TIME) in various cancers, such as colon cancer 29 , clear cell renal cell carcinoma 30 , breast cancer 31 , 32 , lung cancer 33 , 34 , thyroid cancer 35 , adrenocortical adenocarcinoma 36 , bladder cancer 37 , and head and neck squamous cell carcinoma 38 . LncRNA NKILA has demonstrated the ability to initiate apoptosis in tumor-specific T cells, thereby impeding their capacity to infiltrate the tumor, leading to tumor immune evasion 39 .…”
Section: Introductionmentioning
confidence: 99%